70.6k views
5 votes
Someone can help me with this please​

Someone can help me with this please​-example-1

1 Answer

0 votes

Answer:

x = -1 and x = 7

Explanation:

2x^2 + 2x - 14x - 14

2x^2 - 12x -14

Divide through by 2 to simplify the expression

x^2 - 6x - 7

x^2 - 6x -7

Now, let's think of two numbers that when added up gives -6 and when multiplied gives -7

Yes! It's -7 and +1

-7 + 1 = -6 , and -7* 1 = -7

Now, lets substitute these numbers in the expression

x^2 -7x + x - 7

factorize

x(x - 7) + 1(x - 7)

(x + 1) (x - 7)

Now equate to zero

(x + 1) (x - 7) = 0

x + 1 = 0

subtract 1 from both sides

x +1 - 1 = 0 -1

x = -1

Also,

x - 7 = 0

Add 7 to both sides

x -7 + 7 = 0 + 7

x = 7

Hence, x = -1 and x =7

User Zelleriation
by
5.6k points